Let's talk about snooping - Berry, Joy Wilt.; Costanza, John (Chicago : Childrens Press, 1985)
Explains what snooping is and why it is better not to snoop but to respect other people, their property, and their privacy.
3.8
K-3
Keywords: Values -- Juvenile literature; Human behavior -- Juvenile literature; Values; Behavior; Values; Human behavior